The moral branding of Fairtrade: Opportunities and pitfalls of visual representations in the Fairtrade system – empirical insights on the perspectives of German consumers - Braun, Boris; Gröne, Katharina (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
The Fairtrade system can be considered as one of the most successful real-world experiments of alternative economies. However, Fairtrade more than other alternative economic approaches relies on mass market mechanisms and the sale of its products via conventional distribution channels and retail outlets. To gradually transform the ‘unfair’ mechanisms of world trade and to achieve its social and environmental goals, Fairtrade requires a constant growth in sales. This also means that the marketing of Fairtrade goods in the consumer countries is subject to established capitalist mechanisms of advertising and demand creation. Although Fairtrade’s brand building aims at differentiation through alternative values of cooperation, trust, and fairness, it also works within the constraints of simplified and abridged advertising messages. More often than not, contrasts and stereotypes are over-emphasized – a phenomenon that critics call the ‘exploitation of difference’. In this way, new forms of ‘distancing’ and ‘othering’ are constantly built up and reinforced. Individuals, livelihoods, production practices, and entire landscapes in the Global South become commodified and are used for brand development and sales promotion. This paper examines these issues based on interviews and a questionnaire survey among German consumers. Our empirical insights indicate that the visual language used for Fairtrade marketing has to be targeted to critical consumers, who are increasingly skeptical of overly moralizing and simplified images with exaggerated contrasts between the ‘different worlds’ of producers in the South and consumers in the North. However, it should also be noted that Fairtrade Germany is increasingly aware of challenges in its visual communication and is intensively reflecting on its visual language.